An Analysis of the Implementation of Artificial Intelligence (AI) in School-Based Learning - Muqorobin, Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly reshaped various sectors, including education. In school-based learning environments, AI is being increasingly adopted to support diverse pedagogical and administrative functions. This study investigates the implementation of AI technologies in primary and secondary schools, with a focus on their impact on teaching practices, student engagement, and institutional management. Through a mixed-methods approach combining systematic literature review and qualitative interviews with educators across four countries (Indonesia, India, Finland, and the United States), this paper provides a nuanced analysis of how AI tools—such as intelligent tutoring systems, predictive analytics platforms, natural language processing (NLP), and automated assessment systems—are being deployed in classrooms. The results demonstrate that AI contributes positively to personalized learning experiences, enhances the efficiency of assessment and feedback mechanisms, and aids in streamlining school administration. However, the study also highlights persistent challenges, including disparities in infrastructure, ethical dilemmas related to data privacy and algorithmic bias, as well as a lack of comprehensive teacher training in AI integration. The research emphasizes the importance of human-centered AI design that supports—not supplants—teachers, and calls for inclusive policy frameworks that ensure equitable access and ethical use of AI in education. Recommendations include targeted professional development, stakeholder collaboration, and the incorporation of ethical guidelines in the deployment of AI systems in schools. This study contributes to the growing body of knowledge on AI in education and offers practical insights for policymakers, educators, and researchers aiming to harness AI's full potential while mitigating its risks.